Implementasi Model Problem Based Learning Berbantuan Media Animasi Untuk Meningkatkan Hasil Belajar Materi Teks Narasi - Amalia, Fairuz Intan; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was conducted because it was motivated by the lack of interest of students in studying narrative texts in class VI of SD Negeri Kerokan Temanggung. Based on the results of observations that have been made at Kerokan Temanggung Elementary School, specifically in class VI, it is known that the material included in the easy class, class VI students still have less interest in understanding and reading narrative texts, due to the lack of teacher variation in providing learning and the lack of innovation which makes students seem bored. The method used in this research is descriptive qualitative with data collection techniques in the form of observation, interviews, pre-test, post-test and documentation. From the results of the research conducted, it was seen that the pre-test and post-test results increased by 32%.